Opportunities for the applications of FMEA Model in logistics processes in Bulgarian enterprises - Vodenicharova Maria (Logistics & Sustainable Transport, 2017)
The article explores the use of FMEA method in the logistics processes in manufacturing plants in Bulgaria. The surveyed enterprises have a system ISO 9001 and apply different methods of analysis and assessment of logistics processes. The purpose of this study is to present a model for improving the reliability of logistics processes through the FMEA (Failure Mode and Effect Analysis) method.